Analysis of the flexural behavior of pavers made from recycled plastic: with a combination of high-density polyethylene (HLPE), low-density polyethylene (LDPE) and polypropylene (PP) - Giraldo Toro, Alfonso; Nieves Pimiento, Nayive; Hurtado Cortés, Luini Leonardo (Ingeniería Solidaria, 2024)
Introduction: This paper entails an analysis of flexural behavior of pavers made from recycled plastic; a combination of high-density polyethylene (HLPE), low-density polyethylene (LDPE) and polypropylene (PP), carried out in the period 2022 to 2023, with the academic support of the Universidad Distrital Francisco José de Caldas, Sede Tecnológica; Bogotá - Colombia. Problem: To perform flexural tests and analyze the behavior of pavers made from recycled plastic. Objective: To calculate the Flexural Strength (Re), Maximum Stress, Maximum Breaking Load (Cmax), Modulus of Rupture (Mr), Young’s Modulus, for a sample of 15 paving blocks made from HLPE, LDPE, PP and compare with the NTC 2017 standard. Methodology: 15 flexural tests were performed on the specimens selected for the study, and calculations were made for their respective analysis. Results: For flexural strength, the NTC 2017 standard establishes ranges of 3.8 to 4.2 MPa for individual tests and 4.2 to 5 in grouped tests; for the study carried out, a range of 10.8965 ≤ flexural strength (MPa) ≤ 13.5987 was found. Conclusion: Tests indicate that recycled plastic pavers have a higher modulus of rupture than conventional pavers. Originality: Due to the lack of existing information on the subject of paving stones, it is original to carry out a study of paving stone flexural strength and to evaluate the behavior compared to the standard. Limitations: Did not perform electron microscopy analysis on the material.